A novel high-volume Photochemical Emission Aging flow tube Reactor (PEAR). Issue 3 (4th March 2019) - Ihalainen, Mika; Tiitta, Petri; Czech, Hendryk; Yli-Pirilä, Pasi; Hartikainen, Anni; Kortelainen, Miika; Tissari, Jarkko; Stengel, Benjamin; Sklorz, Martin; Suhonen, Heikki; Lamberg, Heikki; Leskinen, Ari; et al.
Abstract: Aerosols emitted from various anthropogenic and natural sources undergo constant physicochemical transformations in the atmosphere, altering their impacts on health and climate. This article presents the design and characteristics of a novel Photochemical Emission Aging flow tube Reactor (PEAR). The PEAR was designed to provide sufficient aerosol mass and flow for simultaneous measurement of the physicochemical properties of aged aerosols and emission exposure studies ( in vivo and in vitro ). The performance of the PEAR was evaluated by using common precursors of secondary aerosols as well as combustion emissions from a wood stove and a gasoline engine. The PEAR was found to provide a near laminar flow profile, negligible particle losses for particle sizes above 40 nm, and a narrow residence time distribution. These characteristics enable resolution of temporal emission patterns from dynamic emission sources such as small-scale wood combustion. The formation of secondary organic aerosols (SOA) in the PEAR was found to be similar to SOA formation in a smog chamber when toluene and logwood combustion emissions were used as aerosol sources. The aerosol mass spectra obtained from the PEAR and smog-chamber were highly similar when wood combustion was used as the emission source. In conclusion, the PEAR was found to plausibly simulate the photochemical aging of organic aerosols with high flow rates, needed for studies to investigate the effects of aged aerosols on human health. The method also enables to study the aging of different emission phases in high time resolution, and with different OH-radical exposures up to conditions representing long-range transported aerosols. Copyright © 2019 American Association for Aerosol Research